Roles of lactate and base deficit in predicting traumatic coagulopathy. - Wook Tae Yang; Il Jae Wang; Suck Ju Cho; Seok-Ran Yeom; Sung-Wook Park; Won Ung Tae; Tae Sik Goh; Up Huh; Dongman Ryu; Chanhee Song; Young Mo Cho (PLoS ONE)
Timely and accurate initial assessment of trauma patients can significantly affect future outcomes. This study aimed to compare the predictive value of the lactate level and base deficit for traumatic coagulopathy, in-hospital mortality, and massive transfusion. This retrospective, observational, single-center study included patients who visited a trauma center from 2016 to 2020. The primary outcome was traumatic coagulopathy, and the secondary outcomes were in-hospital mortality and massive transfusion. Logistic regression analysis was performed to determine whether the lactate level and base deficit were independent risk factors. The area under the receiver operating characteristic curve was calculated to assess the predictive value of lactate and base deficit. In total, 4,379 patients were included in the study. In the logistic regression analysis, base deficit was identified as an independent risk factor for traumatic coagulopathy, whereas lactate was not. Regarding in-hospital mortality, the lactate level was an independent risk factor, whereas base deficit was not. The area under the curve values for predicting traumatic coagulopathy using lactate levels and base deficit were 0.710 (95% confidence interval [CI], 0.696-0.723) and 0.756 (95% CI, 0.743-0.769), respectively; this difference was statistically significant (p < 0.0001; 95% CI, 0.030-0.0622). Base deficit excelled in traumatic coagulopathy prediction, whereas lactate levels prevailed in mortality prediction. Both markers warrant careful observation in the assessment and management of patients with trauma.